A New Approach to Asymptotic Behavior for a Finite Element Approximation in Parabolic Variational Inequalities. (7th July 2011) - Boulaaras, Salah; Haiour, Mohamed
Abstract : The paper deals with the theta time scheme combined with a finite element spatial approximation of parabolic variational inequalities. The parabolic variational inequalities are transformed into noncoercive elliptic variational inequalities. A simple result to time energy behavior is proved, and a new iterative discrete algorithm is proposed to show the existence and uniqueness. Moreover, its convergence is established. Furthermore, a simple proof to asymptotic behavior in uniform norm is given.